Pedati Kuno Krangkeng: Kasepuhan Cirebon Palace Assets Stranded in Indramayu - Nansha, Hendhy; Sachari, Agus; Sabana, Setiawan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Sultan Sepuh IV Amir Sena was the first sultan who dared to criticize the Dutch. Since then, there has been turmoil of resistance from the Cirebon people. The resistance continued until the leadership of Sultan Sepuh V Muhammad Shofiuddin. Until one day Shofiuddin was betrayed and shot by the Dutch when he accepted the offer to negotiate. The unstable government condition in 1786 made Pangeran Suryanegara (the younger brother of Sultan Sepuh V) and his other brothers to leave and fight from outside the palace. The village of Krangkeng was one of the areas that was used as a base for resistance by Prince Suryanegara and his troops. They also brought the palace treasures and heirlooms by using two carts. One of these carts was left in the Krangkeng area and then the site was known as the Pedati Kuno Krangkeng. The Pedati Kuno Krangkeng Site is currently in a damaged condition and is not maintained. This paper aims to revive the story so that it can be noticed and if necessary reconstructed by the authorities. This paper is qualitative in nature and is written with an ethnographic approach through oral history to find out its history and a visual narrative approach to obtain a picture of the original form of the Pedati Kuno Krangkeng. Data collection was obtained through observation, interviews, and literature studies. This paper presents the current state of the Ancient Cart which is very inattentive. In fact, ancient vehicle artifacts such as this cart are relics that we must protect. If it is ignored and not paid attention, the Pedati Kuno Krangkeng in the future may not be witnessed by the next generation. In fact, this cart is one of the important artifacts in the history of Cirebon.